LEGAL TEXT AS A HYPERTEXT: INTERTEXTUALITY OF TRANSLATED INTERNATIONAL LAW RELATED TO TRAFFICKING IN HUMAN BEINGS - BIEL, Łucja (Comparative Legilinguistics, 2013)
The paper examines the intertextuality of translated legislation with a case study of international legal instruments combating trafficking in human beings. The instruments come from three systems (United Nations, Council of Europe and European Union) and are interrelated both by explicit references and implicit textual quotes, the latter being most evident in uniform definitions of trafficking in all the documents. The paper identifies four types of relations in translation, i. e. 1) relations between source texts, 2) relation between the source text and the target text, 3) relations between existing translations, and 4) relations between the target text and target-language legislation. Drawing on Mattila’s metaphor of a legal text as a hypertext, the author shows that translation creates a non-symmetrical hypertext due to partial distortion of interrelations between source texts on the one hand and through new intertextual relations due to recontextualisation and lack of standarisation, on the other hand. The intertextual relations in translation have been found to be more complex and less predictable. Translations demonstrate a surprisingly high variation of equivalents of identical prefabricated terminological units; and low textual fit to non-translated legislation in Polish.